Terahertz spectroscopy of amorphous WSe2 and MoSe2 thin films - Duesberg, Georg (My University, 2018)
Time domain spectroscopy is used to determine the THz electromagnetic response of amorphous transition metal dichalcogenides WSe2and MoSe2 in thin-film form. The dielectric function is obtained using a rigorous transmission model to account for the large etalon effect. The Drude–Smith model is applied to retrieve the dielectric function, and from there, the sample conductivity.
Keywords: THz time domain spectroscopy; Transition metal dichalcogenides; Dielectric function; Absorption; Refractive index